Predictive value of a fragmented QRS complex in diagnosing patients with myocardial ischemia. Issue 3 (19th February 2019) - Cho, H. J.; Yoon, J. Y.; Kim, N.; Jang, S. Y.; Bae, M. H.; Lee, J. H.; Yang, D. H.; Park, H. S.; Cho, Y.; Chae, S. C.
Abstract : Background: A fragmented QRS complex (fQRS) is caused by conduction abnormalities of the ventricle secondary to myocardial ischemia and/or scar in patients with myocardial infarction. However, the implications of the fQRS in the development of coronary artery disease with myocardial ischemia in those without a scar remain unknown. Methods: We studied electrocardiograms (ECGs) obtained from 150 patients (60.5 ± 8.5 years, 102 men) with myocardial ischemia, which was confirmed by performing both, a nuclear exercise stress test and coronary angiography. We also studied ECGs obtained from 601 patients (58.5 ± 10.0 years, 315 men) who showed a negative nuclear exercise stress test (control group). Patients in whom the nuclear exercise stress test showed a myocardial scar were excluded. Results: An fQRS was more commonly observed in patients with myocardial ischemia (n = 48, 32.0%) than in the control group (n = 133, 22.1%) ( P = 0.011). The sensitivity, specificity, positive, and negative predictive values of fQRS in diagnosing myocardial ischemia were 32.0, 77.9, 26.5, and 82.1%, respectively. The fQRS (odds ratio 1.580, 95% confidence interval 1.020‐2.446, P = 0.040) was an independent predictor of myocardial ischemia after adjusting for age, sex, current smoking habits, ST‐T changes on ECG, as well as histories of hypertension, diabetes, and dyslipidemia. Moreover, the fQRS showed an incremental prognostic value over conventional risk factors ( χ 2 = 5, P = 0.032) and over a combination of conventional factors and ST‐T changes ( χ 2 = 9, P = 0.014). Conclusions: The fQRS is a moderately sensitive and independent predictor of myocardial ischemia.